Estética e metafísica da luz em Marsilio Ficino - Silva, Leila Maria de Jesus da (2021)
Marsilio Ficino's philosophy is marked by a predominantly binding aspect, in which all themes come together in a single movement: from good to good. The objective of this research is to demonstrate how in this whole process the theme of light represents the link that crosses and unites all the aesthetics and metaphysics of the fiorentino master under three perspectives that are revealed both in his way of expressing the world and in your conception of it or interact with it. Firstly, it is intended to show that the philosopher of light assumes poetic rationality as an adequate instrument for the interpretation of his original cosmology. Later, it develops from the recovery of fictional figures from the mythological figures of the three graces, - the Beauty (Pulchritudo), the Love (Amor) and the Pleasure (Voluptas) - the way in which light seems to trigger the dance of the universe, marked by the intense dialectic of the lover (Creature) and the beloved (Creator). The present investigation concludes by approaching the solar therapy proposed by Ficino, as a symbol of the human capacity to recognize in the mirror of the world, and in itself, the splendor of the divine face.